Frog Skin Microbiota Vary With Host Species and Environment but Not Chytrid Infection - Kruger, Ariel (Frontiers in Microbiology, 2020)
Describing the structure and function of the amphibian cutaneous microbiome has gained importance with the spread of Batrachochytrium dendrobatidis (Bd), the fungal pathogen that can cause the skin disease chytridiomycosis. Sampling amphibian skin microbiota is needed to characterize current infection status and to help predict future susceptibility to Bd based on microbial composition since some skin microbes have antifungal capabilities that may confer disease resistance. Here, I use 16S rRNA sequencing to describe the composition and structure of the cutaneous microbiota of six species of amphibians. Frog skin samples were also tested for Bd, and I found 11.8% Bd prevalence among all individuals sampled (n = 76). Frog skin microbiota varied by host species and sampling site, but did not differ among Bd-positive and Bd-negative individuals. These results suggest that bacterial composition reflects host species and the environment, but does not reflect Bd infection among the species sampled here. Of the bacterial OTUs identified using an indicator species analysis as strongly associated with amphibians, significantly more indicator OTUs were putative anti-Bd taxa than would be expected based on the proportion of anti-Bd OTUs among all frog OTUs, suggesting strong associations between host species and anti-Bd OTUs. This relationship may partially explain why some of these frogs are asymptomatic carriers of Bd, but more work is needed to determine the other factors that contribute to interspecific variation in Bd susceptibility. This work provides important insights on inter- and intra-specific variation in microbial community composition, putative function, and disease dynamics in populations of amphibians that appear to be coexisting with Bd.